ALQURAN KALAMULLAH MUKJIZAT TERBESAR RASULULLAH SAW - Idham Khalid (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2017)
The Qur’an is a miracle of the Prophet Muhammad. which serves to legitimize his apostolate. Human reason cannot accept his position as an Apostle without bringing proof of his apostleship from Allah in the form of miracles. Therefore, every Apostle has miracles as a prophetic sign and his message. Without that miracle, humans would not believe in them. Although the high moral character of the Prophet and the importance of the message he brought, or the high level of intellect, or position, is still not enough to express his apostolate to humans. The Qur'an is not a divine book, nor is it a legal book, but a guidebook for humans. The authenticity of the Qur’an is guarded by Allah SWT. since the first revealed to the Prophet Muhammad until the end of time. Therefore, the Qur'an does not experience irregularities, changes and disconnections from the sanad as happened in the previous books.